2009
DOI: 10.1002/jrs.2466
|View full text |Cite
|
Sign up to set email alerts
|

Polarised IR and Raman spectra of non‐centrosymmetric Na3Li(MoO4)2· 6H2O crystal—a new Raman laser material

Abstract: Polarised IR and Raman spectra of Na 3 Li(MoO 4 ) 2 · 6H 2 O single crystal were measured. Discussion of the results is based on the factor group approach for the trigonal R 3c(C 3v 6 ) space group with Z = 2. The assignment of the observed bands was performed on the basis of their polarisation behaviour and literature data. The obtained results for the spontaneous Raman scattering were used in the analysis of the stimulated Raman spectra of the material studied -a new Raman laser crystal. The promoting modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…6 can be coarsely divided into two parts: a low frequency part between 100 cm −1 and 250 cm −1 in which the bands are associated with lattice phonon modes, and a high-frequency part from 250 cm −1 to 1000 cm −1 , which is assigned to the internal motions of oxo-anion groups (MoO 4 2− tetrahedron or MoO 6 2− octahedron). [72][73][74][75][76] As discussed in the structure analysis part, except for K The stretching vibrations ν 1 and ν 3 in ideal MoO 4 2− are located in the region 700-1000 cm −1 , while the bending vibrations (ν 2 and ν 4 ) are situated in the region 300-500 cm −1 . 76 When it comes to a specific structure, however, due to crystal field effects, the MoO 4 2− groups are distorted, and therefore the number of possible modes is increased.…”
Section: Raman Analysismentioning
confidence: 86%
“…6 can be coarsely divided into two parts: a low frequency part between 100 cm −1 and 250 cm −1 in which the bands are associated with lattice phonon modes, and a high-frequency part from 250 cm −1 to 1000 cm −1 , which is assigned to the internal motions of oxo-anion groups (MoO 4 2− tetrahedron or MoO 6 2− octahedron). [72][73][74][75][76] As discussed in the structure analysis part, except for K The stretching vibrations ν 1 and ν 3 in ideal MoO 4 2− are located in the region 700-1000 cm −1 , while the bending vibrations (ν 2 and ν 4 ) are situated in the region 300-500 cm −1 . 76 When it comes to a specific structure, however, due to crystal field effects, the MoO 4 2− groups are distorted, and therefore the number of possible modes is increased.…”
Section: Raman Analysismentioning
confidence: 86%
“…reported on the vibrational properties of mirabilite, Na 2 SO 4 ‐10H 2 O and the rediscovered metastable heptahydrate, Na 2 SO 4 ‐7H 2 O . Polarized IR and Raman spectra of Na 3 Li(MoO 4 ) 2 ‐6H 2 O single crystal were measured by Hanuza and coworkers . The results for the spontaneous Raman scattering were used in the analysis of the stimulated Raman spectra of the material studied – a new Raman laser crystal.…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…Caurant et al (2010) proposed that the wide and intense band observed in the 898-913 cm À1 range of the Raman spectra for all borosilicate glasses containing MoO 3 is due to the symmetric stretching vibration of Mo-O bonds of molybdate tetrahedra. Hanuza et al (2010) considered the bands centered at 872 and 912 cm À1 to be assigned to the symmetric stretching vibration and the asymmetric stretching vibration, respectively, of MoO 4 tetrahedra. The band at 328 cm À1 results from the bending vibration of MoO 4 tetrahedra.…”
Section: Resultsmentioning
confidence: 99%
“…K 2 Mo 4 O 13 ) consisting of MoO 6 octahedral units, terminal bonds having a double-bond character, Mo O, are stabilized and the stretching vibrations due to Mo O bonds give the Raman bands at 960-1000 cm À1 (Sekiya et al, 1995;Seguin et al, 1995). On the other hand, it is known that the symmetric and the asymmetric stretching vibrations of MoO 4 tetrahedral units show Raman bands at 895-950 and 810-880 cm À1 (Hanuza et al, 2010(Hanuza et al, ,1999Seguin et al, 1995;Basiev et al, 2000;Saraiva et al, 2008;Luz-Lima et al, 2010). From the Raman spectra of both the glass and the solution, there are no bands at 960-1000 cm À1 .…”
Section: Resultsmentioning
confidence: 99%